Alpha-Synuclein Strain Variability in Body-First and Brain-First Synucleinopathies - Just, Mie Kristine; Gram, Hjalte; Theologidis, Vasileios; Jensen, Poul Henning; Nilsson, K. Peter R.; Lindgren, Mikael; Knudsen, Karoline; Borghammer, Per; Van Den Berge, Nathalie (Frontiers in Aging Neuroscience, 2022)
Pathogenic alpha-synuclein (asyn) aggregates are a defining feature of neurodegenerative synucleinopathies, which include Parkinson’s disease, Lewy body dementia, pure autonomic failure and multiple system atrophy. Early accurate differentiation between these synucleinopathies is challenging due to the highly heterogeneous clinical profile at early prodromal disease stages. Therefore, diagnosis is often made in late disease stages when a patient presents with a broad range of motor and non-motor symptoms easing the differentiation. Increasing data suggest the clinical heterogeneity seen in patients is explained by the presence of distinct asyn strains, which exhibit variable morphologies and pathological functions. Recently, asyn seed amplification assays (PMCA and RT-QuIC) and conformation-specific ligand assays have made promising progress in differentiating between synucleinopathies in prodromal and advanced disease stages. Importantly, the cellular environment is known to impact strain morphology. And, asyn aggregate pathology can propagate trans-synaptically along the brain-body axis, affecting multiple organs and propagating through multiple cell types. Here, we present our hypothesis that the changing cellular environments, an asyn seed may encounter during its brain-to-body or body-to-brain propagation, may influence the structure and thereby the function of the aggregate strains developing within the different cells. Additionally, we aim to review strain characteristics of the different synucleinopathies in clinical and preclinical studies. Future preclinical animal models of synucleinopathies should investigate if asyn strain morphology is altered during brain-to-body and body-to-brain spreading using these seeding amplification and conformation-specific assays. Such findings would greatly deepen our understanding of synucleinopathies and the potential link between strain and phenotypic variability, which may enable specific diagnosis of different synucleinopathies in the prodromal phase, creating a large therapeutic window with potential future applications in clinical trials and personalized therapeutics.